Ost, Reno County - Hein, Rachel (Kansas State University, The Chapman Center for Rural Studies, 2016)
This is a brief history over the German Catholic community of Ost in Sumner Township, Reno County, Kansas. Ost was a settlement built on the faith and persistence of the settlers that founded the town. This study uses plat maps, photographs of past and present Ost, on-site cemetery research, newspaper articles, and the St. Joseph's Church Centennial book.
Rachel Hein, “Ost, Reno County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/175.
Keywords: Reno County; Ost; Cheney; St. Joseph Catholic School; Sumner Township; Red Jaw Valley